Formalization of jobs and firms in emerging market economies through registration reform - Melanie Khamis (IZA World of Labor, 2014)
Informal firms make up a major share of the economy in most developing countries. Expanding formalization could increase government tax revenues, boost firm profits and national income, and increase employee well-being by improving access to social security and health and workers' benefits. Reforms to encourage firms to register include simplifying procedures, reducing the cost and time to register, and making more information available on registration procedures. Reforms might not result in higher registration and formalization.In some cases, better enforcement and wider development policies might be needed as well.
Keywords: O17; O20; 330; informal sector; registration process; information; simplification; cost reduction